Comparison Of Return On Assets, Return On Equity, And Loan To Deposit Ratio In Banking Before And After Mergers And Acquisitions - Fani Puspita Sari; Rivatul Ridho Elvierayani; Abidah Dwi Rahmi Satiti (Jurnal Scientia, 2024)
Aims to determine empirically whether there are differences in bank financial performance before and aftermergers and acuisitions using return on assets (ROA), return on equity (ROE) and loan to deposit ratio (LDR). This research was conduced on banking companies listed on the IDX that carried out mergers and acquisitions in 2008-2019. This study used quantitative approach method by conducting descriptive statistics and inferential statistics. The hypothesis test in this study uses the Wilcoxon Signed Rank Test as a difference test. The results of this study show that there is no significant difference in return on assets (ROA) and return on equity (ROE) before and after mergers and acquisitons while in loan to deposit ratio (LDR) there are significant differences before and after mergers and acquisition.